LEARNING THE ELEMENTS OF COMBINATORICS - Sultanova Umida Akmaljonovna (Web of Journals Publishing, 2024)
Combinatorics is a branch of mathematics that deals with the systematic calculation, arrangement, and arrangement of objects. It plays a crucial role in various fields such as computer science, statistics and engineering.
Keywords: combinatorics, rule, method, number, task, number of substitutions.